Ventilator-associated events in children: a review of literature - Mohd Ali, Noor Azizah; Jauncey-Cooke, Jacqueline; Bogossian, Fiona (Elsevier Ireland Ltd, 2019)
Background: The complexity and variation in ventilator associated pneumonia (VAP) definitions in paediatrics may pose threats to the reliable identification of VAP. The revision of the surveillance definition to ventilator-associated event (VAE) has been mandated in adult populations, to overcome these issues. However, the evidence for application of the definition is unknown in children.